Pengaruh Penggunaan Media Gambar Terhadap Hasil Belajar IPS Siswa SDN 81 Palembang - eka yuliana; Destiniar Destiniar; Sunedi Sunedi (Departement of Mathematics Education, 2023)
This study aims to determine whether there is an effect of the use of image media on the social studies learning outcomes of SDN 81 Palembang students. This research method uses quantitative methods, namely research that emphasises the amount of data collected. Basically the view of the role of value, then the quantitative approach sees everything as never value-free, objective and must be as it is. The results of quantitative research are presented in the form of mathematical calculation results. The data collection techniques used were observation, interviews, and documentation. Data analysis techniques use learning outcomes analysis and image media analysis. Based on the results of research and discussion of the Effect of the Use of Image Media on Social Studies Learning Outcomes of SDN 81 Palembang Students. The increase occurred in the pretest and posttest with evidence of an increase in: 1). The use of quantitative methods can, increase student success on the material types of economic activities. 2). Through the application of quantitative methods with props in accordance with the material can improve student learning outcomes, 3). The percentage of student learning completeness has increased significantly after the improvement of learning there are 27 students out of 35 students. In the improvement of learning on the evaluation of learning improvements there are 9 students on the improvement of pretest learning increased, students who scored 70 and above became 27 students or 65% of 35 students and on the improvement of the pretest to 81%.